Opportunities and challenges in revitalizing rural livelihoods through agro-enterprise development insights from institutional players in the Philippines - Colting-Pulumbarit, Clarice; Jimena, Carla Edith; Mendoza, Maria Emilinda T.; Visco, Emilia S.; Montes, Nimfa Beatrice D.; Cabardo, Jewel Joanna S. (2018)
This article provides a developing country perspective on the strengths, weaknesses, opportunities, and threats to agro-enterprise development (AED) as a strategy for revitalizing rural livelihoods. Institutional players in the Philippines were interviewed and project documents were reviewed. Re- sults show that the key strength of AED is its ability to enhance the capitals under the Sustainable Livelihoods Framework (SLF), promoting the enhancement of rural livelihoods. However, it was also found to be highly capital-intensive and requires substantial investment in time and resources. Nev- ertheless, the increasing demand and low supply of some agricultural commodities and the vast labor force potential in rural areas are opportunities for agro-enterprises. It would be strategic for government and other institutions to build on the strengths and maximize the opportunities to sustain the gains of AED in revitalizing rural livelihoods. Documentation of best practices and an in-depth study of impacts on participating rural-based organizations is suggested to determine effective ways to utilize AED in promoting sustainable rural livelihoods.
Keywords: New agricultural enterprises; Rural development -- Philippines